Hepatoprotektif Ekstrak Batang Bajakah (Spatholobus littoralis Hassk) Induksi Tetraclorida (CCL4) - Mustika Sari; Nawawi Nawawi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the benefits of bajakah (Spatholobus littoralis Hassk) through the study of its utilization as a hepatoprotector. This research method is quantitative. Bajakah stem extract was made using 96% ethanol solvent using the maceration method. Analysis was carried out using liver histology preparations to determine the HAI (Histology Activity Index) Knodel Score. The treatment group consisted of 5 groups, namely, a) negative control (K1) treated with toxic doses of CCL4; b) positive control, namely vitamin E 46.8 mg/KgBW; c) P1 (treatment 1) was 750 mg/KgBW of Bajakah stem extract; d) P2 (treatment two) was 1200 mg/KgBW of pirated stem extract; e) P3 (treatment of three) was extract of the stem of Bajakah 1500 mg/KgBB. The results showed that the post hoc LSD test results in the P1 group had a histopathological picture of damaged liver, there was a significant difference with the K and P3 groups (p <0.05), but there was no significant difference when compared with the P2 group. Meanwhile, the P3 group had significant differences when compared to all groups (p <0.05). In conclusion, the administration of extract of pirated stems at a dose of 1,500 mg/Kg has a significant effect on the HAI value on the average number of hepatocytes with parenchymatous degeneration and necrosis after CCL4 induced Keywords: Bajakah, CCL4, Hepatoprotective